Qualidade fisiológica de sementes de Brachiaria spp submetidas a condições de armazenamento - Tonini, Michelle (2014)
Brachiaria spp. seeds are important to the business sector in Brazil, since these forages are largely used, mainly on cattle feeding. It has been a period the sector has grown significantly, commanding the largest domestic and international trading areas. Thus, an increasing demand has been required concerning the supply of seeds with good quality. In order to keep seeds vigor and germination, it is essential a logistic process that involves up from yield until storage. In this context, this work aimed at studying the packaging influence during Brachiaria brizantha e Brachiaria humidicola spp. seeds storage under different temperatures. So, three kinds of packaging (paper, plastic and woven polypropylene) and two temperature conditions (25 °C and cooling) were applied, while seeds were stored for 210 days. The evaluations were monthly obtained for the following parameters: quality of thousand seeds mass, moisture content, germination in sand, dry weight in seedling, viability by tetrazolium test and germination percentage. In order to evaluate the existence of dormancy in seed samples, scarification was carried out with concentrated sulfuric acid to compare data. The results showed that the packaging did not affect seed physiological quality. However, it is necessary to evaluate the initial dormancy before opting for waterproof packaging, because the scarification process may be delayed. The cooling influenced the seeds of Brachiaria Brizantha, Marandu cultivar. It was put forward the development of secondary dormancy, so periods relatively longer for germination were needed. Scarification was effective on breaking dormancy of Brachiaria Brizantha seeds, whose cultivar is Xaraés as well as Brachiaria humidicola, however, when it was applied to seeds with a high germination index, scarification with sulfuric acid has become harmful